Medieval Imagination: Rhetoric and the Poetry of Courtly Love - Kelly, Douglas (Madison, WI University of Wisconsin Press, 1978)
Medieval Imagination examines the poetry of courtly love with unprecedented thoroughness. Douglas Kelly offers detailed analyses of numerous works within a historical, conceptual, and artistic framework to establish the underlying concept of Imagination in courtly poetry. He capitalizes the term to underscore its medieval sense: the poets invention of significant images to represent a certain conception of truth. Imagination, thus, in its metaphorical sense of providing an idea with a suitable representation in an image, permitted an allegory of love in romance and dream vision from the twelfth century on. The techniques employed in Imaginationallegory, personification, metonymy, synecdocheare analyzed in detail as amplification.In addition to his complete coverage of the better-known poets like Guillaume de Lorris, Machaut, and Froissart, Kelly examines the work of such rarely treated writers as René dAnjou and Oton de Grandson, as well as the Echecs amoureux and related medieval Latin writings. The concluding chapters including Charles dOrléans, Chartier, and Christine de Pisan.The later chapters are a rare boon to French scholars in providing a survey of Middle French courtly literature, a little-explored area of scholarship. Kellys documentation is a fresh and useful contribution to the interpretation of this too-often neglected period.The flower of medieval French culture, the poetry of courtly love, is examined with an unprecedented thoroughness in this work. Douglas Kelly offers detailed analyses of numerous works within a historical, conceptual, and artistic framework.
Keywords: Middle Ages (500-1400); Song; Poetry; Rhetoric